THE INFLUENCE OF ZAKAT INFAK SEDEKAH (ZIS) ON UNEMPLOYMENT IN INDONESIA: AUTOREGRESSIVE DISTRIBUTED LAG (ARDL) METHOD - Tunjung Pramesti Zahra; Ilmiawan Auwalin (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the effect of Zakah Infaq Shadaqah (ZIS) funds channeled by the National Amil Zakat Agency/Badan Amil Zakat Nasional (BAZNAS) on unemployment in Indonesia during 2002-2017. The study was conducted using a quantitative approach. The control variables used for this research are Gross Domestic Product (GDP), education level, investment, and government subsidies. The analysis technique used is Autoregressive Ditributed Lags (ARDL). The data in this study were obtained from the Central Statistics Agency page, BAZNAS, and Indonesian State Budget (Anggaran Pendapatan dan Belanja Negara). The research results partially in short term shows that ZIS has a positive and significant effect on unemployment. While partially long-term research results, ZIS has a negative and significant effect on unemployment. Simultaneously, the variable ZIS, GDP, education level, investment, and government subsidies have significant effects in the short and long term on unemployment in Indonesia in 2002-2017.Keywords: Zakat, Infaq, Shadaqah, Unemployment, Gross Domestic Product, Education Level, Investment, Subsidies, BAZNASREFFERENCE Abdullah, M. dan Sapiei, N. S. (2018). Do religiosity, gender and educational background influence zakat compliance? The case of Malaysia. International Journal of Social Economics, 45(8), 1250-1264.Al-Arif, M. N. R. (2010). Efek pengganda zakat serta implikasinya terhadap program pengentasan kemiskinan. Jurnal Ekbisi Fakultas Syariah UIN Sunan Kalijaga Yogyakarta, 5(1), 42-49.Al-Qardhawi, Y. (2011). Fiqh Al-Zakah (Volume 1). Jeddah: King Abudulaziz University.______________. (2011). Fiqh Al-Zakah (Volume 2). Jeddah: King Abudulaziz University.An-Nabhani. (2004). An-Nizham Al-Iqtishadi fi al-Islam, Cetakan VI. Beirut: Darul Ummah.Anshori, M. dan Iswati, S. (2009). Metodologi penelitian kuantitatif. Surabaya: Airlangga University Press.Badan Pusat Statistik. (2018). Keadaan ketenagakerjaan Indonesia Agustus 2018. Jakarta: Badan Pusat Statistik.Handoko, R. dan Patriadi, P. (2005). Evaluasi Kebijakan Subsidi Non BBM. Kajian Ekonomi dan Keuangan, 9(4), 42-64.Jalaludin, H. (2017). Filsafat pendidikan Islam dari zaman ke zaman. Jakarta: Rajawali Pers.Karim, A. A. (2014). Ekonomi Makro Islami. Jakarta: Rajawali Pers.Kurniawan, A. B. (2014). Analisis pengaruh pertumbuhan ekonomi, upahminimum, dan investasi terhadap jumlah pengangguran di KabupatenGresik. Jurnal Ilmiah Mahasiswa FEB. Malang: Universitas Brawijaya.Kurniawati, L. (2017). Dampak penurunan subsidi bahan bakar minyak: analisis sistem neraca sosial ekonomi Indonesia. Jurnal Info Artha, 1(2), 91-110.Mariyanti, T. dan Mahfudz, A. A. (2016). Dynamic circular causation model in poverty alleviation: Empirical evidence from Indonesia. Humanomics, 32(3), 275-299.Nasrullah, M. (2016). Peran zakat sebagai pendorong multiplier ekonomi. Jurnal Hukum Islam, 8(1), 108-119. Nasution, dkk. (2015). Pengenalan eksklusif ekonomi Islam. Jakarta: Prenadamedia Group.Sukirno, S. (2000). Makro ekonomi modern. Jakarta: Penerbit PT Raja Grafindo Persada. ________. (2006). Makroekonomi teori pengantar. Jakarta: PT Raja Grafindo Persada.Sulaiman, A. S. J. (2015). An empirical study on the influence of Islamic values in poverty alleviation. Journal of Islamic Accounting and Business Research, 6(2), 222-243.Swaramarinda, D. R. (2014). Analisis dampak pengangguran terhadap kemiskinan di DKI Jakarta.  Jurnal Ekonomi dan Bisnis (JPEB), 2(2), 63-70.Tambunan, T. (2001). Perdagangan internasional dan neraca pembayaran. Cetakan Pertama. Jakarta: LPFE-UI.Weber, B. A. (2002). The link between unemployment and returns to education: evidence from 14 European countries. Education + Training, 44(4/5), 171-178.Zhang, H., A, R., dan Zhong, Q. (2019). Anti-corruption, government subsidies, and investment efficiency. China Journal of Accounting Research, 12(1), 113-133.